Complex queries over decentralised systems for geodata retrieval. Issue 2 (26th March 2022) - Zichichi, Mirko; Serena, Luca; Ferretti, Stefano; D'Angelo, Gabriele
Abstract: Decentralised systems have been proved to be quite effective to allow for trusted and accountable data sharing, without the need to resort to a centralised party that collects all the information. While complete decentralisation provides important advantages in terms of data sovereignty, absence of bottlenecks and reliability, it also adds some issues concerned with efficient data lookup and the possibility to implement complex queries without reintroducing centralised components. In this paper, we describe a system that copes with these issues, thanks to a multi‐layer lookup scheme based on Distributed Hash Tables that allows for multiple keyword‐based searches. The service of peer nodes participating in this discovery service is controlled and rewarded for their contribution. Moreover, the governance of this process is completely automated through the use of smart contracts, thus building a Decentralised Autonomous Organization (DAO). Finally, we present a use case where road hazards are collected in order to test the goodness of our system for geodata retrieval. Then, we show results from a performance evaluation that confirm the viability of the proposal.